#TITLE_ALTERNATIVE# - LUTHFI RAMDHANI (NIM: 18213031), YUSUF
A city that can give a sense of security and safety, services which can fulfilled the needs, a means to always learning, and a sense of relieve from problems, is the depiction of an ideal city for citizen. However, that kind of condition will be too difficult to be achieved by a city that is full of multidimentional problems. But of course, every single city should always try to improve their services to citizen, towards a better city and becoming closer and closer to being ideal. Therefore, there is a need for a framework that can breaking down several indicators and initiatives which can improve services towards a better city. One concept that is researching a form of an ideal city is smart city concept. Smart city proposes an idea about how Information and Communication Technology (ICT) can help city management, so that city services can be delivered to citizen effectively and efficiently. Several smart city concepts are Garuda Smart City Model, European Union Smart City, and India Smart City. However, ICT is not something mandatory to be applied in the city, as it will depend on the city needs and capabilities on delivering its services. Therefore, the proposed framework, which from now on will be called Kerangka Kerja Inisiatif Teknologi Informasi (KKITI), should consider initiatives which delivered either using ICT or not on improving city services. City indicator is a parameter that is used to measure how improved a city has been on a certain problem domain. Several references will be used as city indicators, which are ISO 37120, Standar Pelayanan Minimal, Garuda Smart City Model, European Union Smart City, and India Smart City. City initiative is a concrete action took by city to fulfil a certain city indicator(s) so that the city services can be improved. City initiatives formulation will apply design thinking concept, from understanding an indicator, brainstrorming initiative ideas, to determine initiative(s) which can fulfil the indicator. KKITI needs to breakdown city indicators and initiatives to their components thoroughly and in a structured manner, as such these components must be analysed. These components are extracted from the initial purposes of KKITI and from several basic components of a framework which is referred from COBIT, TOGAF 9.1, and Zachman Framework. Following the process of analysis and development of KKITI, a total of 12 indicators and 6 initiatives on health domain, 6 indicators and 4 initiatives on public safety domain, and 10 indicators and 5 initiatives on fire and natural disaster domain are produced. Based on the evaluation result, KKITI is successful in fulfilling the needs of its components and proving that it can be used by city government in a structured manner.